Weed Ecology Of Balik Pulau Rice Ecosystem - Abd Aziz, Nadhirah (2017)
The experiment started by soil sampling at four different rice field plots (Pokok Kenanga, PPK Fasa 3, PPK Fasa 1, and Sungai Burung Darat) in Balik Pulau rice field ecosystem. The soil samples were then brought back to USM for further experiments. Three water level conditions [saturated (3 cm), partial (5 cm), and flooded (10 cm)] and one control treatment (0 cm) were applied in this experiment. There were 12 weeds species that emerged in this experiment namely Echinochloa crus-galli (L.) Beauv, Echinochloa colona (L.) Link, Ischaemum rugosum Salibs., Leptochloa chinensis (L.) Nees., Oryza sativa complex (L.), Cyperus difformis (L.), Cyperus iria (L.), Fimbristylis milliacea (L.) Vahl, Lemna minor L., Ludwigia hyssopifolia (G.Don) Exell, Monochoria vaginalis (Burm.F) Presl, and Sphenoclea zeylanica Gaertn.. For weed seedbank method, the highest emergence of weed species in Pokok Kenanga, PPK Fasa 3, PPK Fasa 1, and Sungai Burung Darat plots were M. vaginalis, L. chinensis, E. crus-galli and S. zeylanica respectively. The total number of weed seedlings present in descending order were 86 seedlings for (Pokok Kenanga plot) > followed by 69 seedlings (Sungai Burung Darat plot) > 44 seedlings for (PPK Fasa 3 plot) > and 26 seedlings for (PPK Fasa 1 plot). For direct seeding method, the highest emergence of weed species in Pokok Kenanga, PPK Fasa 3, PPK Fasa 1, and Sungai Burung Darat plots were L. chinensis. In descending order, the total number of weed seedlings that present were 82 seedlings (Sungai Burung Darat plot) > followed by 74 seedlings (PPK Fasa 1 plot) > 42 seedlings (PPK Fasa 3 plot) > and 12 seedlings xvi (Pokok Kenanga plot). For transplanting method, the highest emergence of weeds species were M. vaginalis for (Pokok Kenanga and PPK Fasa 1 plots) meanwhile L. chinensis was highest in (PPK Fasa 3 and Sungai Burung Darat plots). In descending order, the total number of weeds seedlings emerged were 47 seedlings (PPK Fasa 1 plot) > followed by 20 seedlings (Pokok Kenanga plot) > 13 seedlings (PPK Fasa 3 plot) > 6 seedlings for (Sungai Burung Darat plot). The emergence of M. vaginalis and S. zeylanica were broadleaved weeds which are dominant in each experiment meanwhile L. chinensis was a dominant grassy weed in this study. High water level (10 cm) suppressed the seeds in soil seed bank and causes only a few number of weeds germinated. As a conclusion, the grassy and sedges weeds were higher in saturated and partial water level conditions while broadleaved weeds mostly in flooded water level condition.